Cartera vencida de clientes en la empresa Constructora Consvivisa S.A. del cantón Babahoyo en el período 2022. - Posligua Rojas, Freddy Adrian (2023)
This study addressed the issue of overdue accounts receivable in the construction company CONVIVIAL S.A. in the Babahoyo canton during the 2022 period, with the general objective of examining and analyzing accounts receivable in-depth. The research was conducted using a mixed methodology that combined qualitative and quantitative research, including the analysis of financial documents, interviews with the chief financial officer, and the calculation of key financial ratios. Weaknesses in accounts receivable management were identified, the number of overdue accounts was quantified, and its impact on the company's liquidity was assessed. As a result, proactive measures for recovering overdue accounts and improving financial management were recommended